Research prioritisation in preparedness for and response to outbreaks of high-consequence pathogens: a scoping review - Emilia Antonio; Nicolas Pulik; Susan Khader Ibrahim; Adebisi Adenipekun; Shanthi Levanita; Isabel Foster; Dorothy Chepkirui; Eli Harriss; Louise Sigfrid; Alice Norton (BMC Medicine)
Abstract Background Priority setting for research on epidemic/pandemic-prone pathogens is essential for the allocation of limited resources to optimise impact. It involves the identification of gaps in knowledge crucial to effective preparedness and response to outbreaks. This review maps priority-setting exercises, reviews their approaches to research prioritisation and describes associated monitoring and evaluation processes for research priorities on high-consequence pathogens. Methods Using search terms associated with high-consequence pathogens, as defined by the WHO (2020), EMERGE (2019), European CDC (2022) and the Association of Southeast Asian Nations (2021), and research prioritisation, we searched WHO Global Index Medicus; Ovid Medline; Ovid Embase; Ovid Global Health; and Scopus. Grey literature sources were Google Scholar and the WHO websites, complemented by recommendations from stakeholder consultation. Two independent reviewers screened abstracts and full-texts including documents describing research prioritisation activities. Results were analysed using descriptive statistics and narrative synthesis. Results We identified 125 publications presenting priority setting activities on 17 high-consequence pathogens published between 1975 and 2022. Most (62%) were related to SARS-CoV-2, 5.6% to Ebola virus and 5% to Zika virus. Three different broad approaches to setting priorities were identified, most (53%) involved external consultations with experts. Few (6%) indicated plans to monitor progress against set priorities. Conclusions Our results highlight the diversity in research prioritisation practice in the context of high-consequence pathogens and a limited application of the existing standards in health research prioritisation. An increased uptake of these standards and harmonisation of practice may improve quality and confidence and ultimately improve alignment of funded research with the resulting priorities.